The Main Problems In Islamic Education - La Coy; Muhtadi Abdul Mun’im (Penerbit Hellow Pustaka, 2024)
Islamic education as a process of behavior change that occurs in individuals and society, the issue of Islamic education is a very urgent problem and must receive serious attention. If not, it will have a negative impact on the world of Islamic education. Empirical facts about Islamic education today are very alarming, especially the problem of moral decadence that causes damage to the image of Islamic education. Another problem of education is that there is still a dichotomy of science (between general science and religious science, then the narrowing of understanding of Islamic education which only revolves around aspects of ukhrawi life which is separated from aspects of worldly life, or aspects of spiritual life that are separated from physical life. This research using a qualitative approach with the type of library (library research). Other reference sources that still have relevance with the focus of research are: the main problems in Islamic education.